2012
DOI: 10.1007/s00299-012-1258-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two YUCCA flavin monooxygenase genes from cultivated strawberry (Fragaria × ananassa Duch.)

Abstract: In strawberry (Fragaria 9 ananassa Duch.), auxin has been recognized as the main signal molecule coordinating the growth and initiation of ripening of fruits. The molecular mechanism regulating auxin biosynthesis in strawberry remains unknown. This project reports two YUCCA flavin monooxygenase genes FaYUC1-2 isolated from cultivated strawberry. FaYUC1 and FaYUC2 are most homologous to AtYUC6 and AtYUC4, respectively. Significant expression of FaYUC1-2 is found in vegetative meristems and reproductive organs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…In this work, IiYUC6 presented the highest expression level in fruit compared with other tissues. Similar results were observed from strawberry in which FaYUC1-2 might be involved in flower and fruit development processes (Liu et al, 2012). Therefore, our results suggested that IiYUC6 could play an important role in fruit development processes in I. indigotica .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this work, IiYUC6 presented the highest expression level in fruit compared with other tissues. Similar results were observed from strawberry in which FaYUC1-2 might be involved in flower and fruit development processes (Liu et al, 2012). Therefore, our results suggested that IiYUC6 could play an important role in fruit development processes in I. indigotica .…”
Section: Discussionsupporting
confidence: 82%
“…YUCCA ( YUC ) encodes FMOs that could convert indole-3-pyruvate (IPA) to indole-3-acetic acid (IAA) and was identified in Arabidopsis (Kim et al, 2007), Zea mays (Li et al, 2015), Cucumis sativus (Yan et al, 2016), Glycine max (Costa et al, 2016), Triticum aestivum (Li N. et al, 2014), Fragaria × ananassa Duch (Liu et al, 2012), and Oryza sativa (Abu-Zaitoon, 2014). Based on YUCCA protein, a similar sequence from the transcriptome data of I. indigotia was found in the Full-Length CDS DataBase, and the expression patterns of IiYUC6 were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A comparable peak in expression was also observed for YUC1 (8–10 wpf) (Figure 7D), whereas YUC3 was found to be expressed at very low levels in young berries (one and two wpf), but YUC3 transcripts could not be reliably detected in berries 3–16 wpf (data not shown). An increase in the expression of YUC genes, similar to YUC1 , has recently been reported in strawberries, where the transcript accumulation of Fa YUC1 and Fa YUC2 in achenes peaked at the large green fruit stage [73]. In grape berries, the increase in expression of the putative auxin-biosynthesis genes was preceded by high expression levels of the ethylene biosynthesis genes ACS1 (3–7 wpf) and ACO1 (peaking at 7 wpf) (Figure 7D) which confirmed previous results for the expression of ACS/ACO in developing grape berries [12,14,15].…”
Section: Resultsmentioning
confidence: 90%
“…1C), which would result in a 142G . D amino acid substitution within the ATG-containing motif 1 conserved between YUCCA proteins (Liu et al, 2012). A single 628G .…”
Section: Resultsmentioning
confidence: 99%